A Study on the Gap of Health, Safety and Environmental Related Matters Between Employees and Contractors in an Oil and Gas Company, Port Klang - Norli Hisham, Lyana; Sahak, Nurrul Hafeezah; Zainal Abidin, Mohd Khairul Anuar (Progress in Engineering Application and Technology, 2023)
The company develops digital solutions and implement cutting-edge technology to allow the global energy industry’s performance and sustainability. The main core business in Port Klang is maintenance works of the technology provided. While the employees were focusing on equipment service and maintenance, contractors deliver different kind of support such as logistics, integrated facility management and others. At the company, employees have a proper system called Quest to support the deployment of HSE program. With the system, management were able to perform continuous improvement of HSE at workplace. However, contractors do not have access to Quest. This means that they do not have a proper system for hazard reporting, training competency record, competency validation and other HSE related matter. The aim of this study was to identify the gap in method used in maintaining health, safety and environmental related matters practice between employees and contractors and to analyze the usage effectiveness of current system used by employees of the company in Port Klang. Data was taken from the employees and contractors within the company, collected using semi-structured interview and questionnaire. With this research, a system can be endorsed to improve the current safety practice among contractors and as awareness to HSE department together with the line management of the contractors. The outcome from this study showed that the gap of safety practice between employees and contractors were significant. The current system available for employee was effective as the safety culture among employees were better from the contractors. A safety system to maintain HSE related matters should be introduced to the contractors to maintain a good safety practice.